Estudo sobre a tradução de marcadores culturais em três obras de Milton Hatoum com base em corpus paralelo - Reis-Buzzini, Patrícia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research presents a corpus-based study composed of Milton Hatoum´s three novels translated into English: Relato de um certo oriente (1989)/The tree of the seventh heaven (1994)/ Tale of a certain orient (2004), by Ellen Watson; Dois irmãos (2000)/The brothers (2002) and Cinzas do norte (2005)/ Ashes of the Amazon (2008), both translated by John Gledson. We also used a corpus of comparable texts from the Translational English Corpus (TEC) and a reference corpus in portuguese. The research is justified by the importance of studies focusing translators’ tendencies when facing difficulties related to the translation of cultural markers. The main objectives of the research were: to investigate the translation of cultural markers in Hatoum´s novels, analyze and compare the distribution of cultural markers according to cultural domains; compare the use of cultural markers loans in Hatoum´s corpus and TEC´s corpus and develop a glossary of cultural markers. The theoretical and methodological framework is based mainly on the Corpus-based Translation Studies (BAKER, 1993, 1996, 1999, 2000) and on the principles of Corpus Linguistics (BERBER SARDINHA, 2000, 2004, 2009). For the classification and analysis of the data, we also adopted the studies about the cultural domains (NIDA, 1945; AUBERT, 1981, 2006). The research was performed semi-automatically by a combination of analyzis with the aid of the computer program WordSmith Tools (SCOTT, 2007), which provides the necessary tools for collecting data in a corpus of translated texts. The analysis of the translation of cultural markers in the corpus of Hatoum’s novels revealed some trends shown by the translators and the prevailing cultural domains in each novel. Regarding Watson, it was observed that she seems to use more adaptations of cultural markers instead of loans. However, Watson also revealed a preference for the transfer of cultural markers. Gledson tends to use more loans than ...

Esta pesquisa apresenta um estudo de corpus composto por três obras de Milton Hatoum, traduzidas para o inglês: Relato de um certo oriente (1989)/The tree of the seventh heaven (1994)/ Tale of a certain orient (2004), por Ellen Watson; Dois irmãos (2000)/The brothers (2002) e Cinzas do norte (2005)/ Ashes of the Amazon (2008), ambas traduzidas por John Gledson. Também nos valemos de um corpus de textos comparáveis do Translational English corpus (TEC) e de um corpus de referência em portugês. A investigação justifica-se pela importância de pesquisas que identifiquem tendências apresentadas pelos tradutores diante das dificuldades da tradução de marcadores culturais. Os principais objetivos de pesquisa foram: investigar a tradução de marcadores culturais nas respectivas obras de Hatoum em língua de chegada em relação às obras em língua de partida, analisar e comparar a distribuição dos marcadores por domínios culturais; comparar as ocorrências de empréstimo de marcadores culturais no corpus de obras de Hatoum em relação ao corpus de obras do TEC e elaborar um glossário com marcadores culturais. O arcabouço teórico-metodológico fundamenta-se, sobretudo, na proposta dos Estudos da Tradução Baseados em Corpus (BAKER, 1993, 1996, 1999, 2000) e nos princípios da Linguística de Corpus (BERBER SARDINHA, 2000, 2004, 2009). Para realizar a classificação e análise, também adotamos os trabalhos sobre domínios culturais (NIDA, 1945; AUBERT, 1981, 2006). A pesquisa foi realizada semi-automaticamente, por meio de uma combinação de análises com o auxílio do programa WordSmith Tools (SCOTT, 2007), que oferece as ferramentas necessárias para o levantamento de dados em corpus de textos traduzidos. A análise da tradução dos marcadores culturais no corpus de obras de Hatoum revelou algumas tendências apresentadas pelos tradutores e os domínios culturais predominantes em cada ...
Study on the translation of cultural markers in three books by Milton Hatoum based on parallel corpus
Keywords: Hatoum, Milton 1952- Traduções; Linguistica aplicada; Tradução e interpretação - Estudo e ensino; Linguística de corpus; Literatura brasileira - Traduções - História e crítica; Cultura na literatura; Applied linguistics